A strong-field THz light source based on coherent transition radiation - Kang, Yin; Wang, Ruoyu; Chen, Wei; Tu, Lingjun; Zhang, Kaiqing; Feng, Chao (Frontiers in Physics, 2023)
Terahertz (THz) radiation is a powerful tool for exploring various scientific frontiers through THz pump-probe experiments. However, different experiments may require THz radiations with different spectral properties, such as broad-band or narrow-band, which are difficult to be generated by a single light source. In this paper, we propose a THz light source that can produce both types of THz radiations by manipulating the longitudinal profile of an electron beam and exploiting coherent transition radiation. We perform theoretical analysis and numerical simulations based on the parameters of the Shanghai Soft X-ray Free-Electron Laser facility, and the results show that the proposed light source can generate broad-band THz radiation with a pulse energy of 342 µJ and narrow-band THz radiation with a pulse energy of 91 µJ. The proposed light source can offer more flexibility and versatility for FEL users to conduct THz pump-probe experiments.